Phytoremediation Processes of Sasirangan Textile Industrial Wastewater Treatment using Water Hyacinth - Megayulia Nooryaneti; Chairul Irawan; Abubakar Tuhuloula (Jurnal Kimia Valensi, 2022)
The growth of the textile industry, including the Sasirangan textile industry, is increasing yearly, producing large amounts of liquid waste. Generally, this wastewater is discharged into the environment without treatment, becoming a source of environmental pollution. Therefore, it is crucial to reduce these pollutants. Various methods, not only physical and chemical but also biological methods, are available to remediate wastewater. Phytoremediation has provided an economical, environmentally friendly, and aesthetic solution to remediate wastewater. This study aimed to utilize the Water Hyacinth plant as a phytoremediator and determine its effect in reducing Total Suspended Solid and colors in the liquid waste of the Sasirangan textile industry. This research begins by preparing Water Hyacinth plants. Next, the characterization of Water Hyacinth roots using FTIR and SEM. Finaly, the acclimatization of water Hyacinth, followed by a phytoremediation process for 15 days. Based on the results of the characterization of Water Hyacinth roots with FTIR, it shows that Water Hyacinth roots contain functional groups O-H strain, C-H vibrations, C=O strain, C-H deformation, and C-O stretching. Observations with SEM showed that the roots of Water Hyacinth were extremely unstructured and had pores. However, it has cavities which are pores in cellulose. The significant decrease in Total Suspended Solid was at 9 days of phytoremediation, which was 54 mg/L (71.12% removal). The optimum color reduction within 9 days of phytoremediation was 81.5 PtCo (92.26% removal). The presence of these functional groups and pores, strengthened by the analysis of Total Suspended Solid and colors, showed that Water Hyacinth could reduce levels of Total Suspended Solids and colors in the Sasirangan textile wastewater.